PENGARUH KEPEMIMPINAN OTENTIK DAN MODAL PSIKOLOGIS TERHADAP KETERLIBATAN KERJA YANG DIMEDIASI OLEH KEPUASAN KERJA PADA PEGAWAI KANTOR BAPPEDA ACEH - Rahmi Rahmi; Nurlina Nurlina (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to examine the effect of authentic leadership and psychological capital on work engagement mediated by job satisfaction on the employees of the Aceh BAPPEDA Office. This research is a quantitative research, using a questionnaire as a data collection instrument. The population in this study were employees of the Aceh BAPPEDA Office totaling 136 people. The sampling technique used is simple random sampling. Statistical Products and Service Solutions (SPSS) is used as an analytical method to determine the effect of the variables involved. Based on the results of the SPSS analysis, it was identified that authentic leadership has a positive effect on work engagement, psychological capital has a positive effect on work engagement, authentic leadership has a positive effect on job satisfaction, psychological capital has a positive effect on job satisfaction, job satisfaction has a positive effect on work engagement and job satisfaction mediates. authentic leadership on work engagement, job satisfaction mediates the effect of psychological capital on work engagement.